(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
The Institute of Academic Quality Management (IGESCA), attached to the Academic Vice-Rectory of the State Distance University of Costa Rica, through the Electronic Magazine Quality in Higher Education (CAES) is pleased to present the publication corresponding to the twenty-sixth edition, thirteenth volume, number two, November 2022. This edition includes nine articles with authors from universities in six countries such as: Mexico, Colombia, Ecuador, El Salvador, Spain and Costa Rica, which address different topics related to quality in Higher Education Institutions.